On a class of continous flow - Ramon Mogollon (International Journal of Mathematics and Mathematical Sciences)
This paper involves characterizations of a class of continuous flows. The flows considered are those in which the positive prolongation of each point coincides with the trajectory through the point. The characterizations are based on the theory of prolongation.